Exam Ref MD-101 : Managing Modern Desktops - Bettany, Andrew; Warren, Andrew (Microsoft Press, 2019)
Prepare for Microsoft Exam MD-101 -and help demonstrate your real-world mastery of skills and knowledge required to manage modern Windows 10 desktops. Designed for Windows administrators, Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Associate level. Focus on the expertise measured by these objectives: Deploy and update operating systems Manage policies and profiles Manage and protect devices Manage apps and data This Microsoft Exam Ref : Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have experience deploying, configuring, securing, managing, and monitoring devices and client applications in an enterprise environment About the Exam Exam MD-101 focuses on knowledge needed to plan and implement Windows 10 with dynamic deployment or Windows Autopilot; upgrade devices to Windows 10; manage updates and device authentication; plan and implement co-management; implement conditional access and compliance policies; configure device profiles; manage user profiles; manage Windows Defender; manage Intune device enrollment and inventory; monitor devices; deploy/update applications, and implement Mobile Application Management (MAM). About Microsoft Certification Passing this exam and Exam MD-100 Windows 10 fulfills your requirements for the Microsoft 365 Certified: Modern Desktop Administrator Associate certification credential, demonstrating your ability to install Windows 10 operating systems and deploy and manage modern desktops and devices in an enterprise environment. See full details at: microsoft.com/learn.